2017
DOI: 10.1186/s12894-017-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrolithotomy versus retrograde intrarenal surgery for the treatment of kidney stones up to 2 cm in patients with solitary kidney: a single centre experience

Abstract: BackgroundTo compare the treatment outcomes between percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) for the management of stones larger than 2 cm in patients with solitary kidney.MethodsOne hundred sixteen patients with a solitary kidney who underwent RIRS (n = 56) or PCNL (n = 60) for large renal stones (>2 cm) between Jan 2010 and Nov 2015 have been considered. The patients’ characteristics, stone characteristics, operative time, incidence of complications, hospital stay, and sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
9
23
0
1
Order By: Relevance
“…Our results con rmed that PCNL offered a higher SFR than RIRS as well, which was consistent with most published studies [8,20,2]. Zewu et al supposed that the potential reasons for RIRS with a relatively lower SFR may be due to residual fragments that are more likely to represent a cluster of clinically insigni cant fragments and small working channel according literatures [25], as well as a call for the vacuum aspiration stone system for RIRS.…”
Section: Correlation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Our results con rmed that PCNL offered a higher SFR than RIRS as well, which was consistent with most published studies [8,20,2]. Zewu et al supposed that the potential reasons for RIRS with a relatively lower SFR may be due to residual fragments that are more likely to represent a cluster of clinically insigni cant fragments and small working channel according literatures [25], as well as a call for the vacuum aspiration stone system for RIRS.…”
Section: Correlation Analysissupporting
confidence: 91%
“…Percutaneous nephrolithotomy (PCNL) has been increasingly utilized in the treatment of large stone disease (>2 cm) nearing to 80 percent success rates. The technological advancements have remarkable decreased the role of open surgery considerably in the treatment of kidney stones [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple punctures, supracostal access and a longer surgical duration may be needed for complex stones, but these risk factors significantly increase the complication rates of bleeding, fever, and renal function impairment . Other studies reported initial and final SFRs of 35.7–52.1% and 71.7–88.3%, respectively, after PCNL in patients with a SK , which means a balance between higher SFRs and lower complication rates can be attained in large experienced centres. Our lower initial SFR may be attributed to a high stone burden and the high proportion of patients with complex renal calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies comparing PCNL and RIRS for large kidney stones in solitary kidney patients have been reported recently [12][13][14][15]. However, no evaluation outcomes comparing PCNL with RIRS have been published yet.…”
Section: Introductionmentioning
confidence: 99%